Survival of a small reintroduced griffon vulture population in the Apennines: Insights from Global Positioning System tracking. Issue 1 (February 2023) - Monti, Flavio; Serroni, Pietro; Rotondaro, Francesco; Sangiuliano, Alberto; Sforzi, Andrea; Opramolla, Giancarlo; Pascazi, Antonello; Spacca, Samuele; La Civita, Filippo; Posillico, Mario
Conservation translocations ( e. g., restocking, reintroductions) represent efficient tools to prevent the extinction or favouring the return of previously extirpated populations into the wild. Evaluating demographic parameters of translocated populations is a key issue to assess and monitor their conservation status and to provide evidences useful to implement management actions aimed at long-term conservation results. We report first data on survival estimates and related mortality causes for a reintroduced population of Eurasian griffon vultures ( Gyps fulvus ) in the central-southern Apennine, Italy, from satellite telemetry data. Twenty vultures have been fitted with solar-powered Global Positioning System (GPS) tags in Pollino National Park (PNP, southern Italy, N = 9) and Monte Velino Reserve (MVR, central Italy, N = 11). Survival has been estimated on a total amount of 173, 568 GPS fixes from December 2016 to October 2020 (1415 days) using the Fleming-Harrington estimator. Five, out of 20 vultures, died by poisoning (40%), collision with wind turbines (20%) and of unknown causes (40%). Two birds dispersed from MVR to France (though they later came back) and one from PNP to Croatia. Estimated survival rate across the whole study period was 0.709 (±0.11, SE; 0.523–0.961, 95% CI), and annual survival rate was 0.915 (±0.06, SE; 0.846–0.990, 95% CI). No significant differences in survival rates have been detected according to sex or age. As mortality in our study was mainly human-caused, we urge relevant institutions and agencies to strengthen and effectively establish anti-poison strategies, as well as implementing mitigation and prevention measures for the existing and planned wind farms. The establishment of a long-term viable population in the central-southern Apennines will depend upon both lower levels of human-caused mortality and habitat preservation.